Environmental education in the Flint Hills: exploring recreational and educational opportunities for accessible use at Washington Marlatt Memorial Park in Manhattan, Kansas - Vialle, Anna Grace (Kansas State University, 2023)
Many people who experience the Flint Hills never truly understand its full history, the importance of the prairie, and how the ecoregion serves the surrounding community and its opportunities for environmental education. There has been research on the history and purpose of environmental education and ecotourism, but can be a disconnect between the kinds of tourism or educational programming incorporated into a destination, and a failure to recognize that all tourism sites can incorporate environmental education and ecotourism opportunities if they meaningfully connect people to the ecoregion where they reside. This Master’s Report identifies Washington Marlatt Memorial Park (WMMP) as a site with existing outdoor programming but without current plans for the introduction of environmental education, ecotourism, or a nature center. This research provides several possible design solutions that center on a nature center to serve as a community resource for opportunities within the site to improve the human-nature connection for all. Furthermore, this project report emphasizes the historical, cultural, environmental, restorative, and aesthetic value of the Flint Hills Ecoregion and its connection to these educational opportunities. Additionally, this report gives insight into the specific qualities of this site and the connections between WMMP and its biophysical and socio-cultural context. Analysis of relevant literature, exploration of existing conditions related to WMMP, analysis of nature center and ecotourism precedents, and reflections on the way WMMP can help all visitors appreciate the Flint Hills Ecoregion help guide proposed programming and design strategies. Drawing inspiration from precedent studies, relevant education-based design strategies are identified and used to enhance the environmental education and ecotourism opportunities for WMMP. The conceptual design allows WMMP to serve as a highly interactive nature center destination where important recreation and education activities are physically accessible to serve as a community resource.
Keywords: Environmental education; Nature-based tourism; Nature center; Flint Hills ecoregion; Accessibility; Ecotourism